DIPLOMASI INDONESIA DALAM MENYELESAIKAN SENGKETA FIR (FLIGHT INFORMATION REGION) DI ATAS KEPULAUAN NATUNA DENGAN SINGAPURA - Ramadhita Lestari; Den Yealta (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
FIR (flight information region) is a part of regulation of aviation and aviation problem areas infinitely at one state, which means that aviation world would be touching by one and another states, then to achieved safety on aviation regulation is necessary. Flight information region is an air space regulation that flight information service and alerting service are contained in. FIR’s dispute starts with RAN I that hold by ICAO. On RAN I’s meeting said that FIR management in Natuna Islands has been delegated to Singapore because Indonesia couldn’t have ability to manage this FIR effectively. Because of technology and human resources restrictiveness. There’s so many phenomenon that makes Indonesia want to taking back indonesia’s authority on FIR with any efforts.This research theoretically has built with realism perspectives on International Relations and supported by Diplomacy Theory by Harold Nicholson with setting diplomacy and also state analysis. Formulation of all arguments, facts and theoretical framework on this research is guided by qualitative explanation methods. Scope of this research is Singapore’s management on FIR and also Indonesia’s diplomacy to taking back FIR from Singapore.Researcher has formulated an answered-hypothesis that Indonesia’s diplomacy with joint management model to finish this FIR dispute in Natuna Islands with Singapore. Joint management is made to finish this dispute because Indonesia want to make a peace and win-win solution. So joint management diplomacy is used to finish this FIR dispute currently.Key words : FIR, FIR’s Dispute, Diplomacy , Joint Management Diplomacy